EUROPEAN UNION AFTER THE CRISIS: DECLIN OR RENAISSANCE? - O. V. Butorina (Vestnik MGIMO-Universiteta, 2013)
The second challenging period (after the «eurosclerosis» of the 70-th) in the history of European integration has been going on for eight years. Measures taken by the EU institutions prevented the disintegration of the euro area, but the crisis is not over. We distinguish its four main consequences for the integration: 1) growing federalization of the euro zone, 2) a switch from multi-speed to a two- or three-tier integration model, 3) economization of decision-making process in the euro area, and 4) clearer demarcation of borders within the EU and with its neighbours. The rotation in the ECB Governing Council that may start in 2015, is likely to consolidate the leadership of the "hard core" countries in the decisionmaking process. Further communitarization of the economic part of the EMU makes it more difficult for newcomers to join the euro area and practically closes this window of opportunity for the Great Britain. The crisis revealed the objective limits of EU enlargement, the accession of Turkey became hardly realistic, as well as the start of accession negotiations with Ukraine. The return to a sustainable development of the EU countries requires deep modernization of the European economy and society. However, the ways of this modernization has not been determined yet. It is clear that further accumulation of wealth and growing consumption cannot be a solution. The headline targets and indicators of the "Europe 2020" strategy will be implemented only partially. Modernization process will be hampered by the lack of funding for basic science, which occurred due to the end of the "cold war", as well as social factors whose role in the economic progress had been previously underestimated. Upgrading the EU integration strategy will be possible after the elections to the European Parliament and the appointment of the new Commission in 2014.